Habitual Use of Medicinal Plants among a Group of Jordanian Elderly According to Physical Activity and Gender - Safaa A. Al-Zeidaneen ,; Hadil S. Subih ,; Ala’a Al-Bakheit ,; Nahla S. Al-Bayyari ,; Seham M. Abu Jadayil, (Journal of Pharmacy and Nutrition Sciences, 2019)
Introduction: Traditional medicine use has grown significantly in the last few decades around the world. Similarly, in Jordan. The information regarding the percentages of older adults in Jordan who adopt a healthy life-style and consuming medicinal plants along with performing physical activity are limited. Objective: To evaluates the use of medicinal plants among a sample of Jordanian elderly population and the effect of physical activity and gender on their habitual medicinal plants usage. Method: A cross sectional study was conducted on 120 elderly Jordanian (62 women; 58 men) and evaluated for medicinal plant usage. A questionnaire was used for collecting personal, social, anthropometries and lifestyle information including the daily activities through a personal interview by the principal investigator. Results: In this study about 90% of all participates were using medicinal plants and 95% of males and females used medicinal plants were physically active. Females were used medicinal plants (100%) more than male (79.31%), the most medicinal plants used among elderlies were sage (88.33%), thyme (85.00%) and peppermint (81.67%). Conclusion: The study highlight the increasing number of herbal users among Jordanian elderlies especially females and physically active people and alarming about the possible risk associated with herbal/drug interactions among this age group.